Relationship Between Motivation, Health Literacy, Motivation and Leisure-time Physical Activity Levels of Adolescents - Widiyatmoko, Fajar Ari; Pradipta, Galih Dwi; Maliki, Osa; Hudah, Maftukin; Aji, Ilham Purnama (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
Health literacy, defined as the knowledge, motivation and competence to use health information to improve health and well-being, is associated with regular physical activity. However, there is little evidence on whether health literacy is also associated with motivational readiness for physical activity in the general population. The aim of this study was to investigate whether motivational readiness for leisure-time physical activity is associated with Health literacy. Analyses were based on data from 300 adolescents from cross-sectional data. Motivational readiness for leisure-time physical activity was assessed with stages of change for physical activity with a validated set of items. Health literacy was measured with the short form of the European Health Literacy Survey Questionnaire (HLS-EU-Q16) and categorized as low, medium, and high. Regression analysis was used in this study. The results showed a positive relationship between health literacy, motivation and physical activity level with a significance value of 0.000 < 0.005. High health literacy was positively associated with a more advanced phase of motivational readiness for leisure-time physical activity. Therefore, considering health literacy in interventions to increase motivation for leisure-time physical activity may be a useful approach